2019
DOI: 10.1111/ecc.13082
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and quality of life among Jordanian women diagnosed with breast cancer: The role of trait mindfulness

Abstract: Background Patients diagnosed with breast cancer were reported to have high levels of psychosocial distress and poor quality of life (QOL). Mindfulness is believed to improve QOL and reduce psychological distress in various populations, but its unique association with QOL and psychological distress in women with breast cancer has yet to be established. Objectives This study was conducted to examine the relationship of mindfulness with depression, anxiety and QOL of women diagnosed with breast cancer. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…The results of some studies have also shown that mindfulness can increase the quality of life of cancer patients [ 6 , 30 , 31 ]. Past studies have shown that mindfulness training is closely correlated with the development of attentional functions [ 44 ], cognitive flexibility [ 45 ], and problem solving [ 46 ], and such factors can affect and improve patients' condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of some studies have also shown that mindfulness can increase the quality of life of cancer patients [ 6 , 30 , 31 ]. Past studies have shown that mindfulness training is closely correlated with the development of attentional functions [ 44 ], cognitive flexibility [ 45 ], and problem solving [ 46 ], and such factors can affect and improve patients' condition.…”
Section: Discussionmentioning
confidence: 99%
“…Stress can affect the development, progression, and metastasis of cancerous tumors. If the stress experienced by the patient is not managed properly, it will have a great impact on his/her health [ 3 , 4 , 6 ]. The results of clinical studies support the correlation between stressful events and the survival and improvement of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, providing women's health services to vulnerable populations, as well as mental health services for survivors of sexual traumatic events, remains critical. Potential interventions for Jordanians include mindfulness and increased social support, which have been shown to improve psychological well-being and quality of life among Jordanian women with breast cancer (38).…”
Section: Discussionmentioning
confidence: 99%